DYNAMICS OF TRADITIONAL MUSIC IN SOCIETY: A CASE STUDY ON THE STRATEGY OF SILOTUANG HERITAGE IN JAGOI VILLAGE BENGKAYANG REGENCY - Mastri Dihita Sagala; Zakarias Aria Widyatama Putra; Imam Ghozali; Yudhistira Oscar Olendo (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This research aims to describe the existence, dynamics, and strategies of the inheritance of traditional Silotuang music in Jagoi Village, Bengkayang Regency. Using a qualitative approach with case studies, this research reveals that Silotuang remains an important part of various traditional ceremonies and music festivals in the village. However, the socio-cultural dynamics have brought changes to the number of players, the form of the instruments, and the frequency of Silotuang performances. The inheritance strategy implemented so far includes extracurricular activities at school and involvement in the festival. Data were obtained through participant observation, in-depth interviews, and documentation. Data analysis using the interactive Miles and Huberman model, which includes data collection, data condensation, data presentation, and data verification. The validity of the data uses source and technique triangulation accompanied by prolonged observation. The result of this study highlights the importance of Silotuang as a cultural identity and urges continuous efforts from various parties to preserve it. roader efforts in preserving traditional music so that Silotuang remains a cultural heritage that is preserved and sustainable are the hope for further research, and developing the Silotuang instrument in the real of multidisciplinary sciences and creative product development.